Ukrainian community in the United States and the Ukrainian question during the First World War - Olga Sukhobokova (Американська історія і політика, 2017)
The article discusses the activities of ethnic Ukrainians in the United States, directed at solving the Ukrainian question at the time of the First World War and the postwar settlement in the Paris Peace Conference. The attention is focused on uniting Ukrainian social and political organizations in the United States to help their historical homeland and interaction between the Ukrainian diaspora and the US government and society, involving them to help the Ukrainian people.